ESP Teachers: Insights, Challenges and Needs in the EFL Context - Sukying, Apisak; Supunya, Nuntapat; Phusawisot, Pilanut (Theory and practice in language studies, 2023)
This research investigated ESP teachers’ perceptions of the underlying concepts, challenges, and needs of ESP teaching in Thailand. A six-Likert questionnaire and checklist were given to 63 ESP teachers at a Thai government university. An interview was also used to further explore 12 teacher participants’ issues, challenges, and needs in ESP practices. The results indicated that Thai university teachers had a piecemeal understanding of ESP concepts, and they also agreed that ESP practice is a complex and challenging task. Moreover, the current findings indicate that language teachers must work in tandem with the content teachers. Indeed, the results strongly suggest that teachers require professional training in ESP teaching. Overall, ESP teachers must embody the five essential elements of ESP, including a language teacher, a content teacher, a researcher, a course planner and material provider, and a course evaluator.